Sosialisasi Pendirian “Bank Sampah” Bagi Peningkatan Pendapatan Dan Pemberdayaan Perempuan Di Margasari - Kusuma Wardany; Reni Permata Sari; Erni Mariana (Universitas Lancang Kuning, 2020)
The garbage bank has the function of channeling the waste obtained in accordance with the needs and providing an additional economy for the community. This service aims to make the mothers in Margasari Village know about the existence of a garbage bank, waste management techniques so that they are of economic value and are expected to increase the awareness and enthusiasm of mothers to process waste and preserve the environment. The realization of problem solving is carried out in a socialization program on how to establish and benefit the Waste Bank for increasing income and empowering women. The impact of empowering the garbage bank to customers can be said to be still lacking, this is evident from the average income earned by the community in the first three months of Rp. 10,786,00,-.The impact of empowerment for craftsmen and management can increase income with monthly income of around Rp. 900,000,-.